2003
DOI: 10.1038/sj.bjc.6600927
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of cyclooxygenase-2 is accompanied by increased expression of nuclear factor-κB and IκB kinase-α in human colorectal cancer epithelial cells

Abstract: Cyclooxygenase-2 (COX-2) is selectively overexpressed in colorectal tumours. The mechanism of COX-2 induction is not fully understood, but requires de novo messenger RNA and protein synthesis, indicating regulation at the transcriptional level. Sequence analysis of the 5 0 -flanking region of the COX-2 gene shows two nuclear factor-kB (NF-kB) sites. Inhibition of this protein in model cell culture systems attenuates COX-2 expression and implies that NF-kB plays an important role in COX-2 induction. We measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
63
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 46 publications
4
63
1
2
Order By: Relevance
“…These results are in agreement with earlier studies, that found both stromal and epithelial colorectal cells expressing COX-2 in colorectal adenomas (Arnoletti et al, 2005;Pisano et al, 2005;Tatsu et al, 2005) and carcinomas (Battu et al, 1998;Yamashita et al, 2003;Ohta et al, 2006). We have reported earlier (Charalambous et al, 2003), a significant increase of COX-2 expression in malignant colorectal epithelial cells, compared with adjacent normal epithelium. We now report that this difference is not observed in stromal cells.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are in agreement with earlier studies, that found both stromal and epithelial colorectal cells expressing COX-2 in colorectal adenomas (Arnoletti et al, 2005;Pisano et al, 2005;Tatsu et al, 2005) and carcinomas (Battu et al, 1998;Yamashita et al, 2003;Ohta et al, 2006). We have reported earlier (Charalambous et al, 2003), a significant increase of COX-2 expression in malignant colorectal epithelial cells, compared with adjacent normal epithelium. We now report that this difference is not observed in stromal cells.…”
Section: Discussionsupporting
confidence: 83%
“…We have shown earlier that upregulation of COX-2 is accompanied by increased expression of NF-kB-p65 and IKKa in malignant colorectal epithelial cells (Charalambous et al, 2003), supporting the proposal that NF-kB is involved in COX-2 induction in these cells. This was in agreement with earlier model systems that showed expression of COX-2 was mediated by NF-kB in human umbilical vein (Jones et al, 1993) and rheumatoid synoviocytes (Crofford et al, 1997).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Increased NFkB activity has been observed in CRC (Hardwick et al, 2001) and relative resistance to apoptosis has been attributed to high constitutive NFkB activity in other cancers (Bours et al, 1994;Lind et al, 2001;Charalambous et al, 2003). However, we found no evidence that the specificity of the aspirin-NFkB response is related to differential expression of basal IkBa or p65 proteins or their relative expression.…”
Section: Discussioncontrasting
confidence: 60%
“…Overexpression of COX-2 is sufficient to induce tumorigenesis or sensitize mouse skin for carcinogenesis (39,40). Cyclooxygenase-2 expression is regulated through multiple pathways including NF-B, C/EBP transcription factors, and mitogen-activated protein kinases (41)(42)(43)(44)(45)(46). Induction of COX-2 mRNA is regulated by NF-B in macrophages (41)(42)(43)(44).…”
mentioning
confidence: 99%